Design and Implementation of Piping Installation for Catfish Farming in Sampora Village - Karel Octavianus Bachri; Sandra Octaviani; Marsul Siregar; Widodo Basuki; Tajuddin Nur; Christine Natalia (Institute for Research and Community Services, 2020)
Atma Jaya Catholic University of Indonesia has Faculty of Engineering, which is committed to empower its surrounding communities. This empowerment is implemented based on its core values. The present community empowerment activities have been planned through a series of agreements and the main goal of the activities is to develop the entrepreneurship based on the strength of the area. This paper discusses the assistance given by Faculty of Engineering in designing piping installation for supporting aquaponic activities in Desa Sampora. The project was divided into three steps. First, this project focused on observation and data collecting. This first step also involved discussion with experts. Second, it focused on the design process. The result of the first step was used in the design. Third, the design was implemented and installed in the location. All the steps required careful planning to minimize errors. The expected target of these activities was an aquaponic piping design that is feasible to implement to support sustainable and productive entrepreneurship. The final result was piping installation that can grow 120 plants, is easy to clean up, and has area efficiency.